Gla-Rich protein, magnesium and phosphate associate with mitral and aortic valves calcification in Didabetic patients with moderate CKD - Silva, Ana P. (2022)
Accelerated and premature cardiovascular calcification is a hallmark of chronic kidney disease (CKD) patients. Valvular calcification (VC) is a critical indicator of cardiovascular disease and all-cause mortality in this population, lacking validated biomarkers for early diagnosis. Gla-rich protein (GRP) is a cardiovascular calcification inhibitor recently associated with vascular calcification, pulse pressure, mineral metabolism markers and kidney function. Here, we examined the association between GRP serum levels and mitral and aortic valves calcification in a cohort of 80 diabetic patients with CKD stages 2–4. Mitral and aortic valves calcification were detected in 36.2% and 34.4% of the patients and associated with lower GRP levels, even after adjustments for age and gender. In this pilot study, univariate, multivariate and Poisson regression analysis, show that low levels of GRP and magnesium (Mg), and high levels of phosphate (P) are associated with mitral and aortic valves calcification. Receiver operating characteristic (ROC) curves showed that the area under the curve (AUC) values of GRP for mitral (0.762) and aortic (0.802) valves calcification were higher than those of Mg and P. These results suggest that low levels of GRP and Mg, and high levels of P, are independent and cumulative risk factors for VC in this population; the GRP diagnostic value might be potentially useful in cardiovascular risk assessment.